2016
DOI: 10.1017/s0007114516002476
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary changes on distinct components of the metabolic syndrome in a young Sri Lankan population at high risk of CVD

Abstract: South Asian populations are predisposed to early onset of the metabolic syndrome. Lifestyle intervention programmes have demonstrated a reduction in the metabolic syndrome and CVD risk; however, the most effective components of the multi-faceted lifestyle interventions are unknown. We studied 2637 Sri Lankan males (n 1237) and females (n 1380), with a mean BMI of 23·9 (SD 4·2) kg/m 2 , aged 22·5 (SD 10·0) years, who had participated in a 5-year lifestyle-modification programme to examine the effect of dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Failure attributed to conservative treatment of MS is due to development of programmes based on unidirectional therapies, which are promoted and carried out by a single professional group. 4 Different professionals in isolation have found some beneficial short-term results of treating MS, 22 24 among them nursing. 25 , 26 However, recent published tendencies maintain that the approach to achieve long-term efficiency and efficacy for treating MS must be interdisciplinary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure attributed to conservative treatment of MS is due to development of programmes based on unidirectional therapies, which are promoted and carried out by a single professional group. 4 Different professionals in isolation have found some beneficial short-term results of treating MS, 22 24 among them nursing. 25 , 26 However, recent published tendencies maintain that the approach to achieve long-term efficiency and efficacy for treating MS must be interdisciplinary.…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent study suggested that nursing is important for treating this metabolic disorder, with nurses as the leaders of coordination between health teams and community resources and estates. 23 Our research team aimed to work with the patient, and to understand their social, family, and personal reality. Under the philosophy of empowerment, we made the patient responsible for his/her illness, with an interdisciplinary basis, but without nursing as an element of leadership, showed beneficial results in reduction of MS at 12 months.…”
Section: Discussionmentioning
confidence: 99%